2014
DOI: 10.1155/2014/850831
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infections in Infants Affected by Primary Immunodeficiency

Abstract: Primary immunodeficiencies are rare inherited disorders that may lead to frequent and often severe acute respiratory infections. Respiratory syncytial virus (RSV) is one of the most frequent pathogens during early infancy and the infection is more severe in immunocompromised infants than in healthy infants, as a result of impaired T- and B-cell immune response unable to efficaciously neutralize viral replication, with subsequent increased viral shedding and potentially lethal lower respiratory tract infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 64 publications
(70 reference statements)
0
22
1
Order By: Relevance
“…There is a well-defined segment of patients with immune deficiency diseases that require regular infusions of Ig to reconstitute their deficient humoral Ab compartment and who are also extremely susceptible to RSV disease. [43][44][45] With the withdrawal of RespiGam from the market, an important IVIG product in the arsenal for controlling RSV disease in vulnerable populations is no longer available. The improved efficacy of IVIG vs palivizumab against RSV in HSCT patients 17,19 suggested that broader spectrum Ab may be required.…”
Section: Normal Animalsmentioning
confidence: 99%
“…There is a well-defined segment of patients with immune deficiency diseases that require regular infusions of Ig to reconstitute their deficient humoral Ab compartment and who are also extremely susceptible to RSV disease. [43][44][45] With the withdrawal of RespiGam from the market, an important IVIG product in the arsenal for controlling RSV disease in vulnerable populations is no longer available. The improved efficacy of IVIG vs palivizumab against RSV in HSCT patients 17,19 suggested that broader spectrum Ab may be required.…”
Section: Normal Animalsmentioning
confidence: 99%
“…We showed that HPAEpiCs express lower levels of IFN-β in response to dsRNA compared with HBEpCs. This finding may indicate a lesser contribution of AECs in antiviral innate immune responses in lung because 13 of the abundance of professional immune cells in this tissue site.…”
mentioning
confidence: 85%
“…Newborns and infants, particularly those born prematurely, are susceptible to severe viral infections of the lower respiratory tract (LRT) because of the small size of the airways in which airway edema and sloughing of epithelial cells cause atelectasis, subsequent mismatch of ventilation, perfusion and reduced oxygenation [13]. Once a host is exposed to a virus on the surface of the respiratory tract, the antiviral innate immune response is activated, which determines the serum antibody response that prevents progression to LRT infection via virus neutralization [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation with immunoglobulins (IG) has been considered the standard of care for the treatment of patients with a variety of antibody production disorders due to B cell or B and T cell abnormalities, collectively referred to as primary immunodeficiency diseases (PIDDs) [1]. While regular infusions with IG prevent the vast majority of serious bacterial infections within this population, there is no single prophylactic regimen that provides protection against the wide range of viral pathogens to which these patients are susceptible [2][3][4][5][6][7][8]. In the USA, there are several commercially available IG products that meet minimum standards of concentrations of antibodies to diphtheria toxoid (≥1.21 U/mL), measles (≥0.60 CBER reference), and polio (≥0.28 CBER reference) viruses in conformance with the US FDA guidance 21CFR 640 subpart J [9].…”
Section: Introductionmentioning
confidence: 99%